Orchidaceae from the Dom Delgado campus, Federal University of Maranhão, São Luís (MA) - Santos, Kedma Nunes; Oliveira, Miguel Sena; Ribeiro, Jaireslane Ferreira; Knauf, Jens Martin Cutrim; Silva, Maycon Jordan Costa da; Junior, Wagner Ribeiro da Silva; Marinho, Lucas Cardoso; Ferreira, Alessandro Wagner Coelho (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
The floristic surveys carried out in several universities in Brazil are usually focused on tree or shrub species, with few or no citations of Orchidaceae. The aim of this research was to study the Orchidaceae present at the Federal University of Maranhão (UFMA), Dom Delgado campus, São Luís, Maranhão, including information about their habits, flowering season and mainly phorophytes; besides photographic plates, identification key, morphological descriptions and a distribution map of the species. Collections were carried out monthly from July 2019 to June 2022. Thirteen species of Orchidaceae were identified, of which nine were holoepiphytes (69%), three terricolous (23%) and one hemiepiphyte (8%). The data highlight the importance of the existence of these small urban forest fragments for the preservation of local biodiversity.